2016
DOI: 10.1098/rspa.2016.0076
|View full text |Cite
|
Sign up to set email alerts
|

Bounds on the power of proofs and advice in general physical theories

Abstract: Quantum theory presents us with the tools for computational and communication advantages over classical theory. One approach to uncovering the source of these advantages is to determine how computation and communication power vary as quantum theory is replaced by other operationally defined theories from a broad framework of such theories. Such investigations may reveal some of the key physical features required for powerful computation and communication. In this paper, we investigate how simple physical princ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…This, in conjunction with interference being a key resource in the quantum speed-up, suggests that post-quantum interference may allow for a speed-up over quantum computation.Surprisingly, we show that this is not the case-at least from the point of view of the search problem. We consider this problem within the framework of generalised probabilistic theories, which is suitable for describing arbitrary operationally defined theories [5,8,9,13,16,17]. Classical probability theory, quantum theory, Spekkenʼs toy model [15,31], and the theory of PR boxes [25] all provide examples of theories in this framework.…”
mentioning
confidence: 99%
“…This, in conjunction with interference being a key resource in the quantum speed-up, suggests that post-quantum interference may allow for a speed-up over quantum computation.Surprisingly, we show that this is not the case-at least from the point of view of the search problem. We consider this problem within the framework of generalised probabilistic theories, which is suitable for describing arbitrary operationally defined theories [5,8,9,13,16,17]. Classical probability theory, quantum theory, Spekkenʼs toy model [15,31], and the theory of PR boxes [25] all provide examples of theories in this framework.…”
mentioning
confidence: 99%
“…If such non-local states existed, it has been shown that they would make certain tasks involving distributed computing trivial [19,20]. Moreover, recent studies have explored the possibility of computation in postquantum theories [21][22][23][24][25], particularly showing that non-trivial interference in a theory may be used as a resource for computation beyond the known classical limit [25].…”
Section: Introductionmentioning
confidence: 99%
“…Recently a circuit-based model of computation has been defined and studied in a broad operationally-defined framework for physical theories [21,23,24]. Informally, a theory in this framework specifies a set of laboratory devices that can be connected together to form experiments, and assigns probabilities to experimental outcomes.…”
mentioning
confidence: 99%